Social Studies Teachers’ Readiness to Teach the Security Education Theme in the Reviewed Edition of Nigeria’s Basic Education Curriculum (American International Journal of Humanities, Arts and Social Sciences, 2020)
This study analysed Social Studies teachers’ readiness to teach Security Education. 720 practicing Social Studies teachers drawn from 72 Junior Secondary schools in the South Western Nigeria were administered with a structured questionnaire. The data collected were analysed using simple non-parametric statistics. Findings showed that the teachers have a significantly low knowledge and awareness of the components of the Theme-Security Education. However, the teachers’ readiness to acquire additional useful knowledge and skills required for handling Security Education alongside their area of specialisation (Social Studies) was found to be significantly high. The teachers perceived the inclusion of Security Education in the reviewed Curriculum as a development that will create a significantly higher workload for them. Nevertheless, their response showed a relatively high degree of negative disposition towards the handling of the newly introduced Security Education theme in National Values class Based on these findings necessary recommendations focusing on the need for training and organizing workshops for curriculum implementers were suggested.